Petitions and strategies of persuasion in the middle ages : the English crown and the church, c.1200-c.1550 - Smith, Thomas W.; Killick, Helen (York Medieval Press in association with the Boydell Press, 2018)
Late medieval petitions, providing unique insights into medieval social and legal history, have attracted increasing scholarly attention in recent years. This wide-ranging collection brings two approaches into dialogue with each other: the study of royal justice and secular petitions presented to the English crown, and the study of papal justice, canon law and ecclesiastical petitions (emphasising the international dimension of petitioning as a legal device exercising authority across Latin Christendom). In so doing, it crosses the traditional demarcation lines between secular and ecclesiastical systems of justice, of particular importance, given the participation by many litigants and legislators in both of those legal spheres. A major focus is the mechanics of petitioning - who were the intermediaries in this process, and what were the "strategies of persuasion" they employed? The essays also re-examine the relationship between petitioners and their advisors, and the specific legal, rhetorical and linguistic choices they made in the composition of these texts. In doing so, the volume makes an important new contribution to the emerging field of late medieval supplicatory cultures